Perkembangan Teori Akuntansi: Tinjauan Literatur Sistematis (2012–2022) - Azlina Azlina; Najibullah Najibullah; Agustina Agustina (CV. Kalimasada Group, 2025)
This study aims to identify and explore the development of accounting theory over the 2012–2022 period. Using a Systematic Literature Review (SLR) approach, the study analyzes key trends, dominant theories, and the relevance of accounting theory to modern business practices and needs. Data were collected through the Publish or Perish 8 (PoP 8) software, focusing on literature related to normative and positive accounting theory published in reputable journals during this timeframe. The findings reveal that accounting theory has evolved from pragmatic to positive approaches, with each phase contributing significantly to the discipline. Methodological analysis indicates a dominance of qualitative approaches, while quantitative methods still play a crucial role in validating variable relationships. Additionally, international contributions highlight the strong influence of globalization and technology, including Artificial Intelligence (AI), in advancing accounting theory and practice. This study concludes that accounting theory must continue to evolve to address both local and global challenges. A combination of local and global approaches is necessary to develop more relevant, inclusive, and sustainable accounting theories.